Influence of coatings on energy conservation in construction industry: - Sakr, Nancy Abdel Moneim (AUC Knowledge Fountain, 2017)

(untitled)
World energy consumption has increased rapidly in the past few years. Due to population growth, total energy consumption is increasing; a large amount of energy is wasted on the cooling and heating processes in buildings. Ho¬wever, using thermal heating management can minimize costs, heat consumption and create a management system for the heat insulation for buildings. This concept is being implemented through different approaches. Based on analysis and research, there is an evidence in the energy consumption before and after testing and applying construction approaches for thermal heating management in building units. This investigation addresses an evaluation of the influence of external coatings on energy consumption. Coatings are considered one of the smart effective available approaches for energy efficiency. Unfortunately, this approach is not widely applied in the construction industry. It needs more data to prove effectiveness and credibility between people to use it as a smart thermal insulation approach. Two precedents have been analyzed in order to monitor buildings’ heat exposure, and how the buildings will be affected by thermal insulation materials. Data sheets from chemical companies which produce similar coatings are compared with the usual products and the protective thermal products. The New Egyptian Administrative Capital is considered the new heart of Egypt, where energy saving concept is taken into consideration from the beginning. This shows that Egypt is also moving towards achieving the concept of energy conservation. The site visits reveal a potential for energy conservation up to 70% using protective coatings; which can be implemented in Egypt. Furthermore, based on interviews with site engineers and the head of operational projects inside the capital, they are open for studying more effective approaches for energy savings, as it is highly needed; especially, in the ministries’ zone.